Integrated effects of vermicompost with chemical fertilizers on the yield of mustard (Progressive Agriculture, 2020)
Field experiments were conducted in three Agroecological zones (AEZ) at Farmer’s field, Rangpur (AEZ-3), Farmer’s field, Ishurdi (AEZ-11) and BINA farm, Mymensingh (AEZ-9) to investigate the integrated effect of vermicompost and chemical fertilizers (CF) on Mustard (Brassica napus L.) during 2017-18 cropping season to reduce the usage of chemical fertilizer for mustard cultivation. The experiments were carried out with eight treatments and three replications in Randomized Complete Block Design. The treatments for the crops used in the experiments were T1: Native soil fertility, T2:100% chemical fertilizer (CF),T3: 75% CF, T4: 75% CF + Vermicompost (VC) @ 4 t ha-1, T5:85% CF ,T6: 85% CF + VC @ 4 t ha-1 T7: 75% CF +VC @ 2 t ha-1 and T8: 85% CF+VC @ 2 tha-1. Fertilizers applied on the basis of soil test (STB). Application of vermicompost with chemical fertilizer increased the yield attributes and yields of mustard. The treatment T6 (85% CF + VC @ 4 tha-1) gave the tallest plant height, greatest number of pods plant-1 and siliqua pod-1 and maximum seed (1.82, 1.26 and 1.49 t ha-1 at Rangpur, Ishurdi and Mymensingh, respectively) and straw yields of mustard at all the location with the few exception. But the treatment T6 gave the identical results with the treatments T8, T4 and T2. Application of vermicompost also increased the N, P and K uptakes of mustard at all the location. The treatments T6 T8 and T4 gave statistically identical nutrients uptakes to the treatment T2 (100%CF). The results revealed that 75% CF with 4 t ha-1 vermicompost or 85% CF with 2 t ha-1 vermicompost almost equally effective to produce seed yield of mustard which was also comparable with the full dose (100%) of chemical fertilizers (NPKS) in all the location. Therefore 15-25% chemical fertilizer (NPKS) could be reduced either with the application of 75% CF with 4 t ha-1 vermicompost or 85% CF with 2 t ha-1 vermicompost for mustard cultivation.Progressive Agriculture 31 (2): 81-88, 2020